Activity Levels over Four Years in a Cohort of Urban-Dwelling Adolescent Females - Rockette-Wagner, Bonny (Med Sci Sports Exerc, 2017)
PURPOSE: Evidence suggests that female adolescents and those living in urban environments may have lower physical activity (PA) levels compared to their peers. Yet, few studies report PA for urban adolescent females and there is no consensus regarding potential causes for low PA in this subgroup. We examined PA levels, in a large, diverse cohort of 14–17 year old urban-dwelling females and assessed the impact of socio-economic, personal, and neighborhood/environmental factors on PA. METHODS: One week of time-stamped step count data was collected on 926 girls from the Pittsburgh Girls Study (PGS) at four annual visits. Valid recordings (worn at least 10 hours on 3+ days) were examined and compared to normalized step count values from a U.S. population-representative sample. Relationships between important covariates and average steps/day were examined with regression models. RESULTS: Adjusted mean (stdev) step counts/day at baseline were 5,614 (2,434) after controlling for important covariates with less than 6% of girls achieving at least 10,000 steps/day. PGS girls accrued ~45% of their steps during school hours. Age specific, median step counts/day for study participants were similar to the 25(th) percentile of U.S. population normalized values and did not significantly change over follow-up. Non-Hispanic African American race/ethnicity was associated with higher average step counts/day; obesity and a recent childbirth were associated with lower average step counts/day. CONCLUSIONS: Step counts in this cohort of urban adolescent girls were considerably lower than expected for U.S. adolescent females. Targeted efforts to improve PA levels in urban youth should consider the importance of school-based activity while increasing PA opportunities outside of school.